Comparative Analysis of Modified Admoian Decomposition Method and Homotopy Perturbation Mohand Transform Method for Solving Burger’s Equations (European Journal of Pure and Applied Mathematics, 2024)
This article examines the analytical solution for Burger’s equations utilizing MADM and AHPMTM. We compare both analytical methods for convergence. The MADM uses a novel integral transform (the Mohand transform) with the Adomian decomposition method. The MADM solves the proposed problem using series form solutions that quickly converge to the exact solu-tions. The homotopy process with Mohand transformed and accelerated He’s polynomials underlie the novel AHPMTM approach to accelerate the convergence of the homotopy perturbation Mohand transform method (HPMTM). We compare solutions for MADM and AHPMTM to an exact solution. The methodology can be applied to different models in applied sciences and technology.